Study on effect of surfactant concentration of esophageal scaffold - Nur Khalisah Noorman (Nanyang Technological University, 2021)
Objective: The author has conducted series of experiments to investigate the optimal rate of decellularization on porcine esophagi using varied surfactant concentrations with expected retention of folded internal structure and extracellular matrix (ECM) scaffold. Methods: Porcine esophagi, collected from a local abattoir, were treated and decellularized with Sodium Dodecyl Sulphate (SDS) in varying concentrations of 0.2%, 0.5%, 0.8%, 1% and 2% w/v SDS. After decellularization, results were characterized by: 1) visual cross-sectional assessment, 2) DNA quantification and 3) histology study. Results: Esophagus treated with the lowest SDS concentration is not able to reach complete decellularization due to presence of cell remnants in the ECM. On the contrary, esophagus treated in higher SDS concentrations concluded to reach complete decellularization however lost its folded mucosa. An optimum SDS concentration range within 0.5% to 0.8% w/v SDS is determined to be carried out for further studies. Conclusion: Increasing SDS concentration improves decellularization however it is limited to the optimum range. Beyond the stipulated range, it may have adverse effects on the folded internal structure and ECM scaffold.